PENGARUH MODEL PEMBELAJARAN JINGSAW TERHADAP KEMAMPUAN BEKERJA SAMA DALAM SUATU KELOMPOK PADA SMA KELAS 10 GKPI PADANG BULAN KOTA MEDAN - Simanungkalit1, Amelia; Siregar, Ester Yohana; Sitohang, Elfina Damayanti (Unversitas Katolik Santo Thomas, 2024)
Education plays a very important role in various areas of life. Quality education will also create quality human resources. As a result, Indonesian education continues to receive attention and be improved in many ways, including the National Education System Law, the passing of the Teacher and Faculty Welfare Law, as well as changes to the curriculum to suit needs. with the needs of the time. (Hamzah, 2012:135). The quantitative descriptive research method is a method that aims to create a picture or description of a situation objectively using numbers, starting from data collection, interpretation of the data as well as the appearance and results. Research results Based on table 3.9, the results of the Wilcoxon test for the control class pretest and the experimental class pretest show a calculated value of -2.836 and a sig of 0.003, the control class posttest and experimental class posttest show a calculated value of -2.640 and a sig of 0.008, so it can be concluded that There were differences in the results of the jingsaw learning method for the control group and the experimental group before and after being given the jingsaw learning method treatment.